Pengembangan Industri Animasi Malaysia - Kefassada Putranami Charismaraya (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
The animation industry is an industry that provides significant benefits for countries that can develop it. This profit through the animation industry is demonstrated through Japan and the United States. However, this industry is quite difficult to develop for countries that are just starting out. This paper tries to discuss the causes of Malaysia developing the animation industry even though the industry is still relatively new for Malaysia. This research was conducted using qualitative descriptive method where data was collected through the literature study method. By using literature study method, the data collected is secondary data obtained through journals, books, etc. The time limit used by the author is from 2000 to 2023. The results of this paper show that the animation industry brings benefits for increasing cultural diplomacy and economic aspects. At first, Malaysia's ability to start its animation industry was driven by Qatar's initial interest in Malaysian animation. Through this interest, various Malaysian animation studios and animated films began to emerge. After the broadcast in Qatar, Malaysia's broadcasting area starting to expand to various regions and the animated film include cultural aspect. This fact is strengthened by evidence through the appearance of animated films which show Malaysia's desire to build a harmonious national image. Apart from that, the existence of various collaborations between Malaysia and companies or governments of other countries related to the economy is also clear evidence. Malaysia's economic benefits are not only through cooperation, but also through taxes, broadcast animation studios, and performances through cinemas.
Reupload file repositori 30 januari 2026_Kurnadi/Mita
Keywords: Keunggulan Komparatif; Keunggulan Kompetitif